Long-term costs of colorectal cancer treatment in Spain. Issue 1 (December 2016) - Corral, Julieta; Castells, Xavier; Molins, Eduard; Chiarello, Pietro; Borras, Josep; Cots, Francesc
Abstract Background Assessing the long-term cost of colorectal cancer (CRC) increases our understanding of the disease burden. The aim of this paper is to estimate the long-term costs of CRC care by stage at diagnosis and phase of care in the Spanish National Health Service. Methods Retrospective study on resource use and direct medical cost of a cohort of 699 patients diagnosed and treated for CRC in 2000–2006, with follow-up until 30 June 2011, at Hospital del Mar (Barcelona). The Kaplan-Meier sample average estimator was used to calculate observed 11-year costs, which were then extrapolated to 16 years. Bootstrap percentile confidence intervals were calculated for the mean long-term cost per patient by stage. Phase-specific, long-term costs for the entire CRC cohort were also estimated. Results With regard to stage at diagnosis, the mean long-term cost per patient ranged from €20, 708 (in situ ) to €47, 681 (stage III). The estimated costs increased at more advanced stages up to stage III and then substantially decreased in stage IV. In terms of treatment phase, the mean cost of the initial period represented 24.8 % of the total mean long-term cost, whereas the cost of continuing and advanced care phases represented 16.9 and 58.3 %, respectively. Conclusions This study is the first to provide long-term cost estimates for CRC treatment, by stage at diagnosis and phase of care, based on data from clinical practice in Spain, and it will contribute useful information for future studies on cost-effectiveness and budget impact of different therapeutic innovations in Spain.